Fourth report on the excavations of the Roman fort at Richborough, Kent - Bushe-Fox, J.P. (1949)
This is the fourth report of excavations at Richborough, in Kent, England, conducted by J P Bushe-Fox. Included are descriptions of human remains and artefacts such as pottery, coins, buildings and metalwork, together with an account of the methodology used to unearth these.